68Ga-PSMA-11 PET/CT in primary and recurrent prostate carcinoma: implications for radiotherapeutic management in 121 patients - Körber, Stefan A.; Will, Leon; Kratochwil, Clemens; Häfner, Matthias; Rathke, Hendrik; Kremer, Christophe; Merkle, Jonas; Herfarth, Klaus; Haberkorn, Uwe; Debus, Jürgen; Giesel, Frederik L. (Journal of nuclear medicine, 2019)
The present study analyzed the impact of Gallium-68 (68Ga)-labeled prostate-specific membrane antigen-HBED-CC (68Ga-PSMA-11) positron-emission tomography (PET)/computed tomography (CT) on radiotherapeutic management in a large cohort of men with primary or recurrent disease. Methods: This study investigated 121 men with carcinoma of the prostate who underwent 68Ga-PSMA-11 PET/CT as well as conventional imaging. 50 patients were treatment naive, 11 had persistent prostate-specific antigen (PSA) soon after surgery and 60 presented with recurrent PSA following definitive therapy. Changes in TNM classification of malignant tumors (TNM) stage and radiotherapeutic management after 68Ga-PSMA-11 imaging were compared to results achieved with conventional imaging. Results: In total, a change in TNM stage and radiotherapeutic management was observed for 49 patients (40.5%) and 62 patients (51.2%), respectively. In treatment naïve patients, a change in TNM stage and radiotheraeutic plan occurred in 26.0% and 44.0% of the cohort respectively. For patients with PSA persistence or recurrence, TNM and radiotherapeutic management changed in 50.7% and 56.3% respectively. Conclusion: 68Ga-PSMA-11 PET/CT may shortly become an indispensable tool for detecting prostate cancer lesions in treatment-naïve patients as well as in men with recurrent disease or persistent PSA and seems to be very helpful in personalizing radiotherapeutic management to the individual patients’ distribution of disease.